Luminescence quenching of Sm3+ ions in alkali borotellurite glasses - Tuyen, Vu Phi; Do, Phan Van (Communications in Physics, 2016)
The dependence of luminescence intensity on Sm\(^3 + \) ions concentration in alkali borotellurite (ABTe) glasses has been studied. The quenching of luminescence intensity happens around 0.75 mol% concentration of Sm\(^3 + \) ions and it can relate the energy transfer process through cross–relaxation (CR), the CR channels in ABTe: Sm\(^3 + \) have been shown. The method of Van Uitert was used to find the dominant interaction mechanism for energy transfer process.